Interactions between Angiotensin Type-1 Antagonists, Statins, and ROCK Inhibitors in a Rat Model of L-DOPA-Induced Dyskinesia - Andrea Lopez-Lopez; Rita Valenzuela; Ana Isabel Rodriguez-Perez; María J. Guerra; Jose Luis Labandeira-Garcia; Ana Muñoz (MDPI AG, 2023)
Statins have been proposed for L-DOPA-induced dyskinesia (LID) treatment. Statin anti-dyskinetic effects were related to the inhibition of the Ras-ERK pathway. However, the mechanisms responsible for the anti-LID effect are unclear. Changes in cholesterol homeostasis and oxidative stress- and inflammation-related mechanisms such as angiotensin II and Rho-kinase (ROCK) inhibition may be involved. The nigra and striatum of dyskinetic rats showed increased levels of cholesterol, ROCK, and the inflammatory marker IL-1β, which were reduced by the angiotensin type-1 receptor (AT1) antagonist candesartan, simvastatin, and the ROCK inhibitor fasudil. As observed for LID, angiotensin II-induced, via AT1, increased levels of cholesterol and ROCK in the rat nigra and striatum. In cultured dopaminergic neurons, angiotensin II increased cholesterol biosynthesis and cholesterol efflux without changes in cholesterol uptake. In astrocytes, angiotensin induced an increase in cholesterol uptake, decrease in biosynthesis, and no change in cholesterol efflux, suggesting a neuronal accumulation of cholesterol that is reduced via transfer to astrocytes. Our data suggest mutual interactions between angiotensin/AT1, cholesterol, and ROCK pathways in LID, which are attenuated by the corresponding inhibitors. Interestingly, these three drugs have also been suggested as neuroprotective treatments against Parkinson's disease. Therefore, they may reduce dyskinesia and the progression of the disease using common mechanisms.